Evaluation of E-Government System Policies in Timor-Leste From 2017 To 2023 - Hermenegildo Bubun; Utang Suwaryo; Novie Indrawati Sagita (Green Publisher Indonesia, 2024)
Information and communication technology is increasingly developing in the current era, the government is required to issue a policy to prepare and develop it in the government. In this case, the implementation of e-government system policies in Timor-Leste through the central agency of information and communication technology aims to digitize government activities and services towards a modern government and ensure a transparent, effective, and efficient government. In this study descriptive qualitative research methods. Data collection is carried out by interviews, observation, and documentation with the determination of informants determined by purposive techniques or methods. This study shows that the implementation of the e-government system policy in Timor-Leste is still not effective or optimal because there are still factors that become obstacles to its implementation. Furthermore, the central agency of Tic Timor. I.P. still lacks human resources in the field of IT or adequate technical personnel, lacks facilities, and slow or unstable internet networks. The conclusion in the research obtained from the results of this study is that the Timor-Leste government through the central agency Tic Timor. I.P. has tried to develop an e-government policy system but there are still many shortcomings such as human resources in the field of informatics and technology, and low internet networks. The input suggestion given by the researcher is that the government needs to increase the capacity of supervisors and human resources to develop and accelerate the implementation of e-government policies in various government agencies at the central and regional levels.